2008
DOI: 10.1152/ajprenal.00040.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cystathionine-β-synthase activity during renal ischemia-reperfusion: role of pH and nitric oxide

Abstract: Our recent study (Prathapasinghe GA, Siow YL, O K. Am J Physiol Renal Physiol 292: F1354-F1363, 2007) indicates that homocysteine (Hcy) plays a detrimental role in ischemia-reperfusion-induced renal injury. Elevation of renal Hcy concentration during ischemia-reperfusion is attributed to reduced activity of cystathionine-beta-synthase (CBS) that catalyzes the rate-limiting step in the transsulfuration pathway for the metabolism of the majority of Hcy in the kidney. However, the mechanisms of impaired CBS activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 48 publications
5
73
0
Order By: Relevance
“…The same disorder explained decreased biosynthesis of downstream products of transsulfuration (GSx, hTa, and Tau). CBS activity depends on the cellular redox state and is inhibited by NO or acidosis [46] and activated by ROS [45]. The balance between NO and ROS levels was shown as an important mechanism of the response to paclitaxel at low concentration [13,46].…”
Section: Discussionmentioning
confidence: 99%
“…The same disorder explained decreased biosynthesis of downstream products of transsulfuration (GSx, hTa, and Tau). CBS activity depends on the cellular redox state and is inhibited by NO or acidosis [46] and activated by ROS [45]. The balance between NO and ROS levels was shown as an important mechanism of the response to paclitaxel at low concentration [13,46].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from human and animal studies has demonstrated that H 2 S is directly involved in various diseases, including hypertension, atherosclerosis, and end-stage renal disease (42). The cytoprotective effects of H 2 S have been reported in a variety of organs, including the heart, brain, liver, and kidney, against I/R injury (5,37,47). In this study, we determined that the deletion of MsrA induced a reduction in the levels of plasma H 2 S and accelerated the post-I/R decrease of H 2 S in plasma and kidney tissue.…”
Section: Fig 5 Levels Of H 2 S In Plasma (A) and Kidneys (B)mentioning
confidence: 81%
“…Wu et al reported that renal I/R inhibits CBS gene expression mediated by a transcription factor Sp1, leading to the accumulation of homocysteine and the reduction of H 2 S in the rat kidney (46). Previous studies reported that I/R reduces CBS and CSE activities and H 2 S production, leading to increased kidney damage and oxidative stress (37,47). In the heart, Calvert et al reported that CSE gene-transfer and exogenous H 2 S treatment protected the heart against I/R injury by attenuating oxidative stress (5).…”
Section: Fig 6 Expression and Activities Of Cbs And Csementioning
confidence: 99%
“…The interrelation of NO‐H 2 S and their biochemical interactions are complex and currently unclear. While some studies have shown that NO‐H 2 S positively affect each other's production and function,35, 51 other studies report contrarian, if not directly opposite findings 55, 56. Studies have shown that H 2 S has opposing effects on NOS/NO metabolism.…”
Section: Discussionmentioning
confidence: 99%